Mapping of Dynamic Transcriptome Changes Associated With Silica-Triggered Autoimmune Pathogenesis in the Lupus-Prone NZBWF1 Mouse - Bates, Melissa A.; Benninghoff, Abby D.; Gilley, Kristen N.; Holian, Andrij; Harkema, Jack R.; Pestka, James J. (Frontiers in Immunology, 2019)
Crystalline silica (cSiO2) is a widely recognized environmental trigger of autoimmune disease. In the lupus-prone female NZBWF1 mouse, airway exposure to cSiO2 triggers pulmonary ectopic lymphoid neogenesis, systemic autoantibody elevation, and glomerulonephritis. Here we tested the hypothesis that upregulation of adaptive immune function genes in the lung precedes cSiO2-triggering of autoimmune disease in this model. The study include three groups of mice, as follows: 1) necropsied 1 d after a single intranasal instillation of 1 mg cSiO2 or vehicle, 2) necropsied 1 d after four weekly single instillations of 1 mg cSiO2 or vehicle, or 3) necropsied 1, 5, 9, or 13 wk after four weekly single instillations of 1 mg cSiO2 or vehicle. NanoString nCounter analysis revealed modest transcriptional changes associated with innate and adaptive immune response as early as 1 d after a single cSiO2 instillation. These responses were greatly expanded after four weekly cSiO2 instillations. Concurrent with ectopic lymphoid neogenesis, dramatic increases in mRNAs associated with chemokine release, cytokine production, sustained IFN activity, complement activation, and adhesion molecules were observed. As disease progressed, expression of these genes persisted and was further amplified. Consistent with autoimmune pathogenesis, the time between 5 wk and 9 wk post-instillation reflected an important transition period where considerable immune gene upregulation in the lung was observed. Upon termination of the chronic study (13 wk), cSiO2-induced changes in transcriptome signatures were similarly robust in kidney as compared to the lung, but more modest in spleen. Transcriptomic signatures in lung and kidney were indicative of infiltration and/or expansion of neutrophils, macrophages, dendritic cells, B cells and T cells that corresponded with accelerated autoimmune pathogenesis. Taken together, airway exposure to cSiO2 elicited aberrant mRNA signatures for both innate and adaptive immunity that were consistent with establishment of the lung as the central autoimmune nexus for launching systemic autoimmunity and ultimately, kidney injury.